Ultra low dose CT screen-detected non-malignant incidental findings in the Western Australian Asbestos Review Programme - Murray, C.; Wong, P.; Teh, J.; de Klerk, N.; Rosenow, T.; Alfonso, Helman; Reid, Alison; Franklin, P.; Musk, A.; Brims, F. (Wiley-Blackwell Publishing Asia, 2016)
Background and objective: Computed tomography (CT)-based studies of asbestos-exposed individuals report a high prevalence of lung cancer, but the utility of low dose CT (LDCT) to screen asbestos-exposed populations is not established. We aimed to describe the prevalence of indeterminate pulmonary nodules and incidental findings on chest LDCT of asbestos-exposed subjects in Western Australia. Methods: A total of 906 subjects from the Western Australian Asbestos Review Programme underwent LDCT of the chest as part of regular annual review. An indeterminate (solid) nodule was defined as >50mm3 and part-solid/non-solid nodules >5mm. The presence of asbestos-related diseases was recorded with a standardized report. Results: Subjects were mostly (81%) men with a median age of 70years. Fifty-eight (6.5%) participants were current smokers, 511 (56.4%) ex-smokers and 325 (36.4%) never-smokers. One hundred and four indeterminate nodules were detected in 77 subjects (8.5%); of these, eight cases had confirmed lung cancer (0.88%). Eighty-seven subjects (9.6%) had incidental findings that required further investigation, 42 (4.6%) from lower airways inflammation. The majority of nodules were solid, 4-6mm and more common with age. Five hundred and eighty (64%) subjects had pleural plaques, and 364 (40.2%) had evidence of interstitial lung disease. Conclusion: The prevalence of LDCT-detected indeterminate lung nodules in 906 individuals with significant asbestos exposure was 8.5%, lower than many other CT studies. Clinically important incidental findings were found in 9.4%, predominantly related to lower respiratory tract inflammation. LDCT appears to effectively describe asbestos-related diseases and is likely to be an acceptable modality to monitor asbestos-exposed individuals.